2019
DOI: 10.1556/032.2019.69.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional basic income as an instrument for reducing income inequalities. The case of Poland

Abstract: Unconditional basic income (UBI) is the income allotted to all members of society individually, without the need to work. The right to this income and its level are unconditional and independent of the size and structure of households. In addition, the unconditional income is paid regardless of the income of citizens from other sources. The aim of this paper is to provide a theoretical and an empirical analysis of the UBI, with particular emphasis on the genesis and the effects of introducing this mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…At the country level, digital technology is making it easier to deliver cash transfers to rural recipients, which typify a large proportion of fishers (e.g., [77]). In terms of alleviating poverty, studies have shown that other social assistance initiatives, such as universal basic income (i.e., unconditional monetary transfers from the government to every individual in a society) can help stave off poverty for households at the margins of society [78] and address existing economic and social inequalities [79,80]. An important point here is that for any subsidy reform, there is a need to carefully consider tradeoffs, especially the impact on vulnerable groups [45].…”
Section: Discussionmentioning
confidence: 99%
“…At the country level, digital technology is making it easier to deliver cash transfers to rural recipients, which typify a large proportion of fishers (e.g., [77]). In terms of alleviating poverty, studies have shown that other social assistance initiatives, such as universal basic income (i.e., unconditional monetary transfers from the government to every individual in a society) can help stave off poverty for households at the margins of society [78] and address existing economic and social inequalities [79,80]. An important point here is that for any subsidy reform, there is a need to carefully consider tradeoffs, especially the impact on vulnerable groups [45].…”
Section: Discussionmentioning
confidence: 99%